Minimising the impact of IPv6 neighbour discovery messages on energy consumption in small objects networks. Issue 4 (1st July 2018) - El Ksimi, Ali; Leghris, Cherkaoui
Abstract : Nowadays, it is important to evaluate the use of IPv6 wireless networks. Indeed, the implementation of IPv6 mechanisms and features must be examined. IPv6 requires many objects exchanges like IPv6 routing information which could be communicated by different messages multicast. These messages are too frequent; they could impact energy consumption related to battery‐powered objects. Therefore, the energy consumption is nowadays, one of the most important issues in small object networks with IPv6. Thus, the aim of this study is to suggest a new algorithm called minimising energy consumption under connectivity constraint. The performance evaluation is based on several parameters that would help in maintaining connectivity between the mobile objects and their default router. The results showed that energy consumption could be minimised by optimising IPv6 multicast messages. Overall, this method results a significant effectiveness and might be used as a future wireless networks improvements.